Semiconductor nanostructures quantum states and electronic transport - Ihn, Thomas (Oxford : Oxford University Press, 2010)
This introduction to the physics of semiconductor nanostructures and their transport properties emphasizes five fundamental transport phenomena: quantized conductance, tunnelling transport, the Aharonov-Bohm effect, the quantum Hall effect and the Coulomb blockade effect.
Description based on print version record.
Includes bibliographical references.
Keywords: Semiconductors; Nanostructures; Transport theory